Quantitative live-cell imaging of secretion activity reveals dynamic immune responses - Mai Yamagishi; Kaede Miyata; Takashi Kamatani; Hiroki Kabata; Rie Baba; Yumiko Tanaka; Nobutake Suzuki; Masako Matsusaka; Yasutaka Motomura; Tsuyoshi Kiniwa; Satoshi Koga; Keisuke Goda; et al. (iScience, 2024)
Summary: Quantification of cytokine secretion has facilitated advances in the field of immunology, yet the dynamic and varied secretion profiles of individual cells, particularly those obtained from limited human samples, remain obscure. Herein, we introduce a technology for quantitative live-cell imaging of secretion activity (qLCI-S) that enables high-throughput and dual-color monitoring of secretion activity at the single-cell level over several days, followed by transcriptome analysis of individual cells based on their phenotype. The efficacy of qLCI-S was demonstrated by visualizing the characteristic temporal pattern of cytokine secretion of group 2 innate lymphoid cells, which constitute less than 0.01% of human peripheral blood mononuclear cells, and by revealing minor subpopulations with enhanced cytokine production. The underlying mechanism of this feature was linked to the gene expression of stimuli receptors. This technology paves the way for exploring gene expression signatures linked to the spatiotemporal dynamic nature of various secretory functions.